Labor Underutilization in the Years Following the GFC: an Australian Example - Mitchell, William; Baum, Scott (My University, 2021)
This paper presents analysis the main factors associated with labor underutilization in Australia during the period following the Global Financial Crisis (GFC). It does so by using a panel data set consisting of survey data taken from the Household, Income and Labour Dynamics Australia (HILDA) and Small Area Labour Markets data, published by the Department of Employment. The results illustrate the broad nature of factors influencing an individual’s risk of being underutilized including the changing nature of macro-economic processes during the post-GFC period.
International Journal of Research in Humanities and Social Studies
Keywords: Labour market